Bilateral Testicular Tumors in a Non-Cryptorchid Dog: Coexistence of Sertoli Cell and Interstitial Endocrine Cell Tumors - Chiti, Eleonora; Fazio, Esterina; Cancedda, Giorgio; Medica, Pietro; Satué , Katiuska (Acta Scientiae Veterinariae, 2022)
Background: Testicular neoplasms in dogs are more frequent than in other animal species, representing the most common tumors in elderly subjects after skin neoplasms. In cryptorchid subjects, the risk of neoplastic degeneration is high. The cytological examination is essential to differentiate the type of neoplasia and to determinate the best diagnostic approach. Aim of this report was to describe clinical and histopathological features of a dog with coexistence of Sertoli cell and interstitial endocrine cell tumors in a non-cryptorchid dog. Case: A 9-year-old non-neutered male dog, German Spitz breed, was presented to the veterinary clinic. On clinical examination, the dog had a body condition (BCS 6/9), pink mucous membranes, capillary refill time (CRT) < 2 sec, lymph nodes of normal size, afebrile, normal heart and respiratory rate. The abdomen was depressible to palpation, without pain, the skin appeared hyperpigmented, with generalized presence of comedones, pendular foreskin and absence of hair at the abdominal level, in the ventral portion of the trunk and neck, scant hair also at the level of the inner thighs and in perianal. At ultrasounds examinations, the right testicle presented a hypoechoic circular focal lesion, in the caudal pole, of 0.7 cm in diameter, well defined, echogenicity and a remnant of normal echostructure, smooth and regular margins; the left testicle showed an increase in size, irregular margins, with a heterogeneous echo structure, given by hypoechoic areas, referred to cysts, hemorrhagic or necrotic areas. The hemogram reported slightly microcytic and normochromic regenerative anemia. The leukogram showed monocytosis. The absence of the typical stress leukogram characterized by neutrophilia, lymphopenia and eosinopenia, and the reduction of ALP allows to rule out Cushing’s disease. In order to rule out hypothyroidism due to the inhibitory effect of estrogens on the release of thyroid-stimulating hormone (TSH) the concentration of total thyroxine was analyzed, reporting normal values excluding hypothyroidism. Blood oestradiol 17-β (E2) concentration was increased, with a normal testosterone (T) concentration of 0.30 ng/mL. Given the suspicion of the presence of testicular tumors, castration was performed by the surgical excision of both gonads, after ruling out the presence of abdominal or pulmonary metastases by chest and abdominal radiography. Discussion: The clinical, histopathological findings supported the diagnosis of testicular tumors. According to the pathological report, both gonads presented parenchymal nodular neoplastic nodular areas referring to the Sertoli sustentacular cells in the right testicle, to the proliferation of Leydig interstitial cells in the left one. The nodule in the left testicle was unencapsulated and showed a solid-diffuse pattern. Neoplastic cells were irregular polygonal, medium to large in size with moderate nucleus/cytoplasm ratio and moderate anisocytosis. In the right testicle, the nodule was heterogeneous in consistency and a diffuse pattern was present. Neoplastic cells were polygonal morphology, had a moderate nucleus/cytoplasm ratio and were organized tubules lined and obliterated the extensive cell growth. Bilateral orchiectomy allowed to improve the clinical signs, and 3 months after surgery, the animal was in good health, with evident improvement skin lesions. The E2 analysis was repeated, detecting normal values, demonstrating that testicular neoplasm in this patient were involved in E2 production; also T concentration decreased considerably from 0.30 to < 0.07 values. Keywords: Sertoli cell tumor, testicular neoplasm, neoplastic cells, Leydig cell tumor, castration, canine.